THE EXPANSION OF DUAL CITIZENSHIP IN THE 21ST CENTURY: TRANSNATIONALISM AND MIGRANTS’ IMAGININGS OF CITIZENSHIP (International Journal of Food and Nutritional Sciences, 2022)
Academic discussions on transnationalism, immigration, and citizenship in the last several years have mainly left out the views of migrants. Changes to conceptualizations of citizenship reflect an increased emphasis on individual rights, as seen by global advances in dual citizenship laws. The shift towards a more open attitude towards dual citizenship has shed light on issues of belonging and exclusion. Explore the similarities and differences in migrant perceptions between these two nations and among migrants. Their fight for freedom of movement across borders, legal protection, and social and political rights depends on national citizenship. However, migrants also know that liberal democratic citizenship's ideals of equality and justice do not always match reality; even naturalized migrants face prejudice. National citizenship is difficult for migrants because of their challenges in balancing their many identities and allegiances, especially regarding issues of belonging and identification with the national society. Despite differences, most migrants can and do identify with more than one community, often expressing a desire to become active members of more than one national group. However, this does not imply that citizenship or individual identities must be deterritorialized.